Hydration In Athletes: A Literature Review - Ahdiyatul Fauza; Widya Astuti (Journal of Applied Food and Nutrition, 2021)
The aim of this study to review the most recent research on the factors that most influence hydration. This study review using the literature research from google scholar, PubMed, and Elsevier. Many athletes after training experience dehydration due to not consuming enough fluids and electrolytes before, during training, and competition. To assess hydration status cannot be determined by just one factor. The general recommendation of hydration status measures using accurate biomarkers to detect body water fluctuations of 3% of total body water (TBW), using dehydration index, body mass, or color of urine. Therefore, monitoring hydration status is very important to maintain athlete performance. Exercise increases hypohydration due to fluid losses so that should be given to fluid supplementation and intake from certain food for each athlete. The factor that most influences the athlete's hydration is sweat loss and fluid intake.